2019
DOI: 10.1016/j.seares.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of long-term variation in offspring metabolism due to BPA in eggs in rainbow trout using the DEB model

Abstract: Bisphenol A (BPA) in eggs prior to fertilization was found to induce long-term metabolic disturbances in juvenile rainbow trout (Oncorhynchus mykiss). Here we describe these imprinting effects in a Dynamic Energy Budget (DEB) framework, which allows interpretation of the data in an energy allocation context. First, DEB parameters for control rainbow trout were optimized using data extracted from 12 studies in the literature. Several modes of action on DEB parameters were then tested in order to correctly predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The consequence of BPA exposure correlates with reductions in behavioural activities (Yokota et al., 2000), cardiovascular function (Schirling, Bohlen, Triebskorn, & Köhler, 2006), development and growth (Aluru, Leatherland, & Vijayan, 2010) and locomotor performance (Little & Seebacher, 2015). BPA exposure during development can also have persistent effects into adulthood via epigenetic modifications (Jašarević et al., 2011), suggesting that short‐term exposures to BPA have lasting consequences on life history (Sadoul, Augustine, Zimmer, Begout, & Vijayan, 2019; Thomas, Birceanu, Sadoul, & Vijayan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of BPA exposure correlates with reductions in behavioural activities (Yokota et al., 2000), cardiovascular function (Schirling, Bohlen, Triebskorn, & Köhler, 2006), development and growth (Aluru, Leatherland, & Vijayan, 2010) and locomotor performance (Little & Seebacher, 2015). BPA exposure during development can also have persistent effects into adulthood via epigenetic modifications (Jašarević et al., 2011), suggesting that short‐term exposures to BPA have lasting consequences on life history (Sadoul, Augustine, Zimmer, Begout, & Vijayan, 2019; Thomas, Birceanu, Sadoul, & Vijayan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, f has been fixed to one during calibration and then estimated for independent data ( Sadoul et al, 2018 ). This approach was not followed in this study as it is based on observed growth rather than feeding data, so the mechanistic basis is unclear.…”
Section: Methodsmentioning
confidence: 99%
“…DEB has been applied to a wide range of taxa, with parameters available in the Add My Pet (AmP) library ( Marques et al, 2018 ). The majority of DEB-TKTD studies thus far have focused on invertebrates ( Ashauer and Jager, 2018 ) and more recently fish ( Zimmer et al, 2018 , Sadoul et al, 2018 ), with very few studies concerning terrestrial vertebrates ( Martin et al, 2019 , Desforges et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The DEB model has been applied to reconstruct environmental concentrations of pollutants that the mussels would have experienced ( van Haren et al , 1994 ). In another study, Sadoul et al (2019) looked at how exposure to Bisphenol A during the egg phase of rainbow trout impairs the growth of adult fish. The authors reconstructed the stress upon metabolism based on observed changes in growth.…”
Section: Diversity and Distribution Of Speciesmentioning
confidence: 99%